Changes in lifestyle and risk of colorectal cancer in the European Prospective Investigation into Cancer and Nutrition - Botteri, E; Peveri, G; Berstad, P; Perez-Cornago, A; Ferrari, P (Lippincott, Williams and Wilkins, 2022)
Introduction: We investigated the impact of changes in lifestyle habits on colorectal cancer (CRC) risk in a multi-country European cohort.